Lipid characterization of red alga Rhodymenia pseudopalmata (Rhodymeniales, Rhodophyta). Issue 1 (13th October 2016) - Peralta‐García, Edith; Caamal‐Fuentes, Edgar; Robledo, Daniel; Hernández‐Núñez, Emmanuel; Freile‐Pelegrín, Yolanda
SUMMARY: Rhodymenia pseudopalmata is a red alga that grows at the Caribbean coast of the Yucatan Peninsula and has been proven successful in cultivation. In this study we present the lipid composition of R. pseudopalmata collected from wild populations during three different seasons of 2013. Cultured material was also analyzed and compared in order to evaluate its value as feedstock for biotechnological uses. Thin layer chromatography, 1 H and 13 C NMR spectroscopy and gas chromatography‐mass spectrometry were used to assess variations in their lipid composition. Our results showed that the dominant lipid classes were phospholipids both in wild and cultured materials. The phospholipids phosphatidylcholine and phosphatidylglycerol and the glycolipid monogalactosyldiacylglycerol were present in both wild and cultured R. pseudopalmata, whereas the phospholipid lysophosphatidylcholine was only found in wild material. Fatty acids (FAs) showed a high monounsaturated FAs (MUFAs) content with oleic acid (C18:1ω9) as the dominant compound (78 and 94% of the MUFAs for wild and culture materials, respectively). Saturated FAs (SFAs) represented approximately 90% of the total fatty acid content, with palmitic acid (C16:0) reaching approximately 83% of the SFA content. Rhodymenia pseudopalmata was low in polyunsaturated FAs when compared to other red algae. Other compounds such as 1‐heptadecene, 1‐hexadecene, 15‐heptadecenal, 3‐eicosene 6, 10, 14‐trimethyl‐2‐pentadecanone, phytol, and heptadecane were also found. Lipid composition differences between the wild and cultured algae suggest that light and nutrients can be manipulated to modify lipid composition. Based on its lipid composition and cultivation feasibility, R. pseudopalmata could be a potential source for nutraceuticals and biofuels production.